2006
DOI: 10.1017/s0022112006001868
|View full text |Cite
|
Sign up to set email alerts
|

Shallow cavity flow in a porous medium driven by differential heating

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. This paper describes steady flow through a porous medium in a shallow twodimensional cavity driven by differential heating of the upper surface. The lower surface and sidewalls of the cavity are thermally insulated. The main emphasis is on the situation where the Darcy-Rayleigh number R is large and the aspect ratio of the cavity L (length/depth) is of order R 1/2 . For a monotonic temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Similarity solutions of the horizontal boundary layer equations on a heated horizontal wall have been discussed by Cheng & Chang (1976) and Chang & Cheng (1983). More recently, the flow generated by differential heating of the upper surface of a rectangular cavity whose other three walls are thermally insulated has been considered by Daniels & Punpocha (2004;2005) and Daniels (2006).…”
Section: Introductionmentioning
confidence: 83%
“…Similarity solutions of the horizontal boundary layer equations on a heated horizontal wall have been discussed by Cheng & Chang (1976) and Chang & Cheng (1983). More recently, the flow generated by differential heating of the upper surface of a rectangular cavity whose other three walls are thermally insulated has been considered by Daniels & Punpocha (2004;2005) and Daniels (2006).…”
Section: Introductionmentioning
confidence: 83%
“…He indicated that viscous coupling effect was negligible through out the normalized saturation range. Steady flow through a porous medium in a shallow two-dimensional cavity was studied by Daniels (2006). He showed that for a monotonic temperature distribution at the upper surface, the problem consisted of an interaction involving the horizontal boundary-layer equations and the vertical boundarylayer equations, which governed the flow near the colder sidewall.…”
Section: Introductionmentioning
confidence: 99%